2008
DOI: 10.1021/jf0716679
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Compost and Its Water-Soluble Fractions

Abstract: A sequential chemical fractionation was applied to a compost, with its dissolved organic matter (DOM) extracted in water and separated in hydrophilic (HiDOM) and hydrophobic (HoDOM) components and a water extract, following oxidation of compost suspension with an oxygen flux (TEA). The components sequentially isolated by mild extractions and hydrolyses as structurally unbound (SU), weakly bound (WB), and strongly bound (SB) to the matrix of the bulk compost and its water-soluble fractions were identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 35 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Assuming >C 18 molecules (MW > 250 g mol −1 ) are dominant in mobilized SOM (ref. 18) and the O/C ratio of ∼0.4 reported here, based on the compilations of Koop et al 5 we estimate a glass transition temperature of SOM of ∼300 K. Therefore, evaporation of water from the SOM-containing mist would result in amorphous solidification (glassy state) at ambient temperatures, consistent with observations of solid spherical ASOP reported here ( Supplementary Fig. 6).…”
supporting
confidence: 91%
“…Assuming >C 18 molecules (MW > 250 g mol −1 ) are dominant in mobilized SOM (ref. 18) and the O/C ratio of ∼0.4 reported here, based on the compilations of Koop et al 5 we estimate a glass transition temperature of SOM of ∼300 K. Therefore, evaporation of water from the SOM-containing mist would result in amorphous solidification (glassy state) at ambient temperatures, consistent with observations of solid spherical ASOP reported here ( Supplementary Fig. 6).…”
supporting
confidence: 91%
“…This suggests that factors beyond physical alteration of seedcoats were responsible for earlier and better germination. Spaccini et al (2008) reported that aerated compost extracts contained low-molecularweight bioactive compounds of microbial origin. Arancon et al (2007) demonstrated that the application of a vermicompost extract to growth media enhanced seed germination and seedling growth of tomatoes and cucumbers.…”
Section: Discussionmentioning
confidence: 99%
“…Vermicompost has shown to stimulate germination of several ornamental and horticultural plant species such as green gram (Phaseolus aureus) (Karmegam et al 1999) with the solid vermicompost, thus suggesting that other factors rather than physical amelioration were responsible for higher germination. A recent study by Spaccini et al (2008) showed that aerated compost extracts contained most of the low-weight compounds associated to a compost matrix, most of them of microbial origin and therefore potentially bioactive substances. Moreover, a further study demonstrated that these extracts produced greater effects in plant physiology than the equivalent bulk compost (Puglisi et al 2008).…”
Section: Discussionmentioning
confidence: 99%